Life of Alexander von Humboldt Compiled in Commemoration of the Centenary of his Birth - Löwenberg, Julius (Cambridge University Press, 1873)
Alexander von Humboldt (1769-1859) was a naturalist, explorer and philanthropist now well known for his multidisciplinary approach to science. First published in English in 1873, this two-volume biography was translated from the German edition of 1872, edited by Karl Bruhns, which had been compiled in commemoration of the centenary of Humboldt's birth. Incorporating numerous extracts of Humboldt's own warmly written letters and anecdotes from his many acquaintances, it charts his travels in South America, Asia and Europe. Volume 2 covers his later life, exploring his impecunious period in Paris at the École Polytechnique, where he shared rooms with the famous French chemist Gay-Lussac, and later, his close association with King Frederick William IV of Prussia. Ideal for students and researchers in the history of science, this is a minutely detailed and compelling insight into the life of the man behind the scientist.